Apolipoprotein A-I mimetic peptides (ApoAI MP) improve oxidative stress and inflammatory responses in Parkinson’s disease mice - Jiang, Hongfang; Bai, Xue (Frontiers in Pharmacology, 2022)
Purpose Parkinson's disease (PD) is closely associated with oxidative stress and inflammatory situation. Apolipoprotein A-I mimetic peptides (ApoAI MP) have antioxidant and anti-inflammatory properties. We aimed to study the therapeutic effect of ApoAI MP on a PD mouse model, and to explore the related mechanisms. Methods A PD mouse model was induced by using 1-methyl-4-phenyl-1,2,3,6-tetrathydropyridine (MPTP). The model mice were treated with different concentrations of ApoAI MP. The open-field behavioral test assesses the total moved distance, the rest time, and the number of crossings, grip strength test was performed to measure grip strength, and Rota-rod was used to evaluate motor coordination. Oxidative stress was identified by measuring the levels of superoxide dismutase (SOD), catalase (CAT), glutathionperoxidase (GSH-Px), malondialdehyde, and H2O2. Inflammatory situation was analyzed by measuring the levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6). Meanwhile, the scavenging activities of ApoAI MP for ABTS, DPPH, hydroxyl radical and superoxide anion were measured. The effects of the peptide on neurotransmitters were evaluated. Results PD model establishment increased oxidative stress and inflammatory status by increasing the concentrations of H2O2 production, and the levels of TNF-α, IL-1β and IL-6 (P<0.05). ApoAI MP intervention improved the activity of the PD model by increasing the total moved distance and the number of crossing the target box, and grip strength (P<0.01), and reducing the falling times from Rota-rod, and rest time (P<0.05). ApoAI MP increased antioxidant properties by increasing the activities of SOD, CAT and GSH-Px, and reducing MDA concentration (P<0.05). ApoAI MP addition reduced oxidative stress by scavenging ABTS, DPPH, hydroxyl radicals and superoxide anion and reducing the concentrations of H2O2 production (P<0.05). ApoAI MP treatment increased anti-inflammatory capacities by reducing the concentrations of TNF-α, IL-1β and IL-6 (P<0.05). HPLC analysis showed that the peptide treatment improved neurotransmitters. Conclusions ApoAI MP improves the behavioral performance of PD mice by improving antioxidant and anti-inflammatory capacities.